Моделирование характеристик деформируемых грунтов в процессе их уплотнения цилиндрическими рабочими органами катков - Vitaly Viktorovich Mikheyev; Serguey Valer'evich Savel'ev (Вестник СибАДИ, 2017)
The article deals with the task of theoretical modeling for elastic properties of soils under compacting action. That problem is of sufficient practical value for selection of optimal working parameters for soil compaction process in building and road construction. The model of interaction between rigid working tool of cylindrical shape and deformable soil is considered in the article. This shape corresponds to the metal drum of road roller and was used to calculate the stiffness of the soil volume which interacts with it. The tangent resistant force which occurs in case of roller’s motion was also calculated.